Discriminative basketball game-related statistics between winning and losing teams in European women's basketball - Jimenez, S.; Gomez Ruano, M. A.; Lorenzo Calvo, A.; Leite, N.; Sampaio, J.; Ortega, E.; Ibanez, S. J. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The aim of the present study was to identify the gamerelated statistic that best discriminate between winning and losing teams in women`s basketball. The sample comprised all 46 games from the 2005 European Championship. The game-related statistics gathered included: 2- and 3-point field-goals (both successful and unsuccessful), free-throws (both successful and unsuccessful), defensive and offensive rebounds, blocks, assists, fouls, steals and turnovers. The results showed that the most successful teams in this championship were those that had less ball possessions per game and achieved greater defensive efficiency , that is less points per ball possessions allowed to the opposite team. The results from the multivariate analysis showed that in all games, the gamerelated statistics that discriminated between both groups were the unsuccessful 3-point field-goals, fouls and assists. In balanced games (final score differences equal or bellow 12 points), the discriminant game-related statistics were the unsuccessful 3-point field-goals, successful freethrows and fouls. In unbalanced games (final score differences above 12 points) the discriminant game-related statistic was the assists. Coaches should be aware that dominating these variables will increase the probability to win games and allow to perform the training process in women`s basketball.